Leadership Roles in Building Resilient University Libraries and a Sustainable Workforce for Enhanced Education in Nigeria - Obinyan, Oluwatoyin; Obinyan, Gabriel Aine (Folia Toruniensia, 2025)
University libraries are pivotal in fostering dynamic and resilient academic environments by facilitating effective learning, teaching and research endeavours. However, the ability of these libraries to fulfil their mandate hinges significantly on visionary leadership. Drawing from the insights of Michael Gibbson and contemporary leadership theories, this article explores the critical role of leadership in enhancing the resilience and relevance of university libraries in Nigeria. It scrutinizes the challenges posed by ineffective leadership, which often stems from issues such as ethnic patronage and compromised selection processes. Moreover, it underscores the necessity for proactive leadership that can navigate the complex terrain of university politics and resource allocation to bolster library collections and services. By examining the relationship between leadership styles and organizational culture, the article emphasizes the importance of cultivating a supportive work environment that fosters innovation and customer satisfaction. Furthermore, it advocates for continuous training and development initiatives to equip library leaders and their staff with the necessary skills to adapt to evolving demands and technologies. The article provides valuable insights for policymakers, administrators and practitioners seeking to strengthen the resilience and efficacy of academic libraries’ leadership in Nigeria and beyond.